Variation Morphologique Adaptative Des Populations De Sarotherodon Melanotheron Des Secteurs IV Et V De La Lagune Ebrié (Côte d’Ivoire) Face Au Stress Chimique - Olivier, Bopo Zadi Sylvain; Paulin, Sokouri Didier; Koco, Nobah Céline Sidonie; Célestin, AtséBoua (European Scientific Journal, ESJ, 2018)
The impact of chemical pollution on organism’s characteristics was assessed through morphological features in IV and V sectors of Ebrié Lagoon using Sarotherodon melanotheron (Rüppel, 1852) as bioindicator. Sampling was carried out during a whole year in three sites (Layo, N’djem and Ahua) characterized by contrasted environments(respectively moderate, medium and high levels of pollution). The morphological studies were based on morphometric biomarkers such as fluctuating asymmetry (FA) and average body shape. Fluctuating asymmetry was evaluated among individuals within sites using ANOVA Procrustes. Average body shape was compared among sampling sites using Principal Components Analysis (PCA), Canonical Variates Analysis (CVA) and MANOVA. Fluctuating asymmetry did not vary between sampling sites. However, the average body shape was significantly different between specimens from Ahua and both those from Layo and N’djem. There was no significant difference between fish from Layo and those from N’djem.Allometric effects and the abiotic parameters influenced, to some extent, the body shape of individuals.A morphological differentiation according to the geographical distance was also observed. The study revealed a morphological adaptation of the populations of S. melanotheron in the study area.